INFLUENCE OF SCIENCE TECHNOLOGY SOCIETY BASED WORKSHEET ON INTEGRATED SCIENCE PROCESS SKILLS OF STUDENTS - Izzaturrohmah, Izzaturrohmah; Dewi, Novi Ratna; Pamelasari, Stephani Diah (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
This research aims to determine the effect of students science activity based on Science Technology Society (STS) of student’s integrated science process skills (ISPS). This research used true experimental design with Pretest-Posttest control design. Samples were taken by using simple random sampling technique from the student population of class 7 SMP N 22 Semarang junior high school in academic year 2017/2018. The resulting class VII B as the experimental class and class VII A as control class. The data were collected by using documentation, test, and observation method. The Result of correlation test between students activity based on STS to student’s ISPS obtained from the observation result obtained correlation coefficient of 0,554. The correlation coefficient is categorized as moderate so it can be interpreted that the students' activity based on STS gives a moderate effect on the student's ISPS. The effect of the students' activity based on STS of the student’s ISPS calculated from r2 x 100% is 31%, r is the correlation coefficient which states the correlation between students activity based STS and student’s ISPS. The result of significance test of correlation coefficient value obtained tcount > ttable , it means that students activity based on STS give positive influence to student’s ISPS. Based on the results of the study, it can be concluded that the students' activity based on STS influenced the student’s ISPS. The N-gain calculation to measure the increase in the experimental and control classes showed that the increase of experiment class was categorized as medium, the increase of the control class was categorized as low.